Analisis Pengaruh Risiko Kredit, Risiko Pasar dan Risiko Operasional Terhadap Profitabilitas pada Bank Umum BUMN yang Terdaftar di BEI Periode 2013-2020 - Nurwihda Jahrotunnupus; Gusganda Suria Manda (Universitas Batanghari Jambi, 2021)
This study aims to look at the influence between credit risk (NPL), market risk (NIM), and operational risk (BOPO) on Profitability (ROA) on state-owned commercial banks listed on the Indonesia Stock Exchange for the period 2013-2020. The sample used by this study is 4 state-owned banking companies. The technique for sampling used is saturated sampling. The analysis method in this study is a multiple linear regression analysis with the help of the SPSS program. The results of the study showed that together or simultaneously credit risk, market risk, and operational risks had a significant effect on profitability in state-owned commercial banks listed on the Indonesia Stock Exchange for the period 2013-2020. Partial research results on credit risk variables (NPLs) had no significant effect and had a negative relationship to profitability (ROA). The results of the study partially on market risk variables (NIM) had a significant and positive effect on profitability and the results of the study in part or partially operational risk variables (BOPO) had a significant effect and had a negative relationship to profitability (ROA) in state-owned commercial banks in the period 2013-2020.